Unilateral Lichen Planus Pigmentosus with Blaschko's Line Distribution: A Case Report - Almuntsrbellah Almudimeegh; Mohammed Habib; Omar Alsuhaibani; Nawaf Alkhudhayri (Karger Publishers, 2023)
Lichen planus pigmentosus (LPP) is a distinctive variant of lichen planus described for the first time in 1974. A wide range of presentations and distribution patterns have been reported, mainly presenting as dark brown hyperpigmented macules and patches, typically involving sun-exposed areas such as the face, neck, and flexural folds. It is more common in dark-skinned patients with a female predominance. Infrequently, LPP may present as a Blaschkoid distribution, with only a few cases reported in the medical literature. We report an unusual case of LPP that developed with a unilateral Blaschkoid distribution on the left side of the trunk in a 32-year-old female following weight reduction surgery.